Trends of Microsurgical Head and Neck Free Flap Reconstruction and Safety during the COVID-19 Pandemic - Valeria P. Bustos; Nicholas Elmer; Anamika Veeramani; Carly D. Comer; JacqueLyn R. Kinney; Samuel M. Manstein; Natalie Hassell; Bernard T. Lee; Samuel J. Lin (Journal of Reconstructive Microsurgery Open, 2024)
Background The coronavirus disease 2019 (COVID-19) pandemic poses unprecedented challenges among patients with head and neck (HN) cancer that require oncological and reconstructive surgeries. This study aims to identify differences in postoperative outcomes for patients who underwent microsurgical HN free flap reconstruction prior to versus during the COVID-19 pandemic.